Evaluación de los fundamentos teóricos y estrategias metodológicas del proceso de enseñanza aprendizaje del baloncesto en los estudiantes de educación básica superior del Colegio NacionalTécnico Ing. José Corsino Cárdenas del cantón Pasaje, provincia de El Oro - Andrade Muñoz, Romel Oswaldo (2015)
In developing this thesis, which is the objective of expanding the discipline of basketball students of the basic cycle, I have seen the importance of this discipline to promote because it is a team sport that can develop both indoor and pool, and the modifications that have occurred until today valuing as a sport that can be practiced throughout the year without being able to disrupt the climate in their skills, now considered as the main Olympic discipline among other sports.